Penerapan Model Blended Learning Dalam Meningkatkan Pemahaman Mahasiswa - Nurul Laily; Muliatul Maghfiroh (Gunung Djati Conference Series, 2022)
The blended learning model is a combined model between offline learning and online learning. Many educators choose to use the blended learning learning model as an effort to improve student understanding, especially in the subject of expertise in the Islamic Religious Education Study Program, Tarbiyah Faculty, IAIN Madura. The purpose of this study, first, is to find out the application of the blended learning model for expertise courses in Islamic Studies Study Program. Second, to analyze the increase in student understanding of skills courses at the Islamic Religious Education Study Program, Tarbiyah Faculty IAIN Madura The research method used in this study is a qualitative research method with a descriptive type of research, in which researchers will compare the level of students' understanding of e-learning-based learning conducted during the Covid-19 pandemic with blended learning. The data sources of this research are the Chair of the PAI Study Program, Lecturers who teach expertise in PAI and students. Based on the results of the study, it shows that First, the application of blended learning is carried out in two events, namely if the number in the class is less than 20 students, the blended process is offline at intervals -alternating with implementing Health Protocols. The second way is if there are more than 20 students in one class, then the first week of odd absences are included, the second week of even absent absences are offline. Second, the use of blended learning learning models can improve student understanding of the Islamic religious education study program IAIN Madura, from using e-learning based learning models (online) due to the pandemic and switching to using blended learning models to make students more interested in learning and further improve student understanding especially in the subject of expertise.